Penicillium citrinum Provides Transkingdom Growth Benefits in Choy Sum (Brassica rapa var. parachinensis) - Keyu Gu; Cheng-Yen Chen; Poonguzhali Selvaraj; Shruti Pavagadhi; Yoon Ting Yeap; Sanjay Swarup; Wenhui Zheng; Naweed I. Naqvi (Journal of Fungi, 2023)
Soil-borne beneficial microbes establish symbioses with plant hosts and play key roles during growth and development therein. In this study, two fungal strains, FLP7 and B9, were isolated from the rhizosphere microbiome associated with Choy Sum (Brassica rapa var. parachinensis) and barley (Hordeum vulgare), respectively. Sequence analyses of the internal transcribed spacer and 18S ribosomal RNA genes combined with colony and conidial morphology identified FLP7 and B9 to be Penicillium citrinum strains/isolates. Plant–fungus interaction assays revealed that isolate B9 showed significant growth promotion effects in Choy Sum plants cultivated in normal soil, as well as under phosphate-limiting conditions. In comparison to the mock control, B9-inoculated plants showed a 34% increase in growth in aerial parts and an 85% upsurge in the fresh weight of roots when cultivated in sterilized soil. The dry biomass of such fungus-inoculated Choy Sum increased by 39% and 74% for the shoots and roots, respectively. Root colonization assays showed that P. citrinum associates directly with the root surface but does not enter or invade the root cortex of the inoculated Choy Sum plants. Preliminary results also indicated that P. citrinum can promote growth in Choy Sum via volatile metabolites too. Interestingly, we detected relatively higher amounts of gibberellins and cytokinins in axenic P. citrinum culture filtrates through liquid chromatography–mass spectrometry analyses. This could plausibly explain the overall growth induction in P. citrinum-inoculated Choy Sum plants. Furthermore, the phenotypic growth defects associated with the Arabidopsis ga1 mutant could be chemically complemented by the exogenous application of P. citrinum culture filtrate, which also showed accumulation of fungus-derived active gibberellins. Our study underscores the importance of transkingdom beneficial effects of such mycobiome-assisted nutrient assimilation and beneficial fungus-derived phytohormone-like metabolites in the induction of robust growth in urban farmed crops.